The Outer Limits of the Continental Shelf : the legal aspects of their establishment - Suarez, Suzette V. (Springer, 2017)
Introduction -- The Continental Shelf Prior to UNCLOS III -- The Continental Shelf – its Definition and Limits under Article 76 of the 1982 United Nations Convention on the Law of the Sea...